POLITIK HUKUM BELANDA DAN KEWENANGAN PERADILAN AGAMA BERDASARKAN STAATSBLAD 1931 NO.53 - ., Widiawati; Fauziah, Tsabita Husna; Azzahra, Sheila Lutfiana (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2023)
The Religious Courts in Indonesia itself was based on the opinions of Dutch legal experts, which is one element of how the authority of the Religious Courts works. The theory of receptie was implemented in the legal politics of Dutch, that became the basis for the enactment of a new decision Staatsblad 1931 No.53. The Staatsblad changed the authority of Religious Courts. This authority was narrowed by removing the authority to resolve inheritance and hadhanah issues for religious courts and transferring it to Landraad. The authority of religious courts was narrowed in Staatsblad 1931 No.53 makes Islamic law even more oppressed. In the end, the religious court did not have absolute authority and was still under the supervision of the district court so that all types of judge's decisions had to be based on the approval of the Landraad or in other words the Dutch authorities.